The SCFA Receptor GPR43 and Energy Metabolism - Kimura, Ikuo; Inoue, Daisuke; Hirano, Kanako; Tsujimoto, Gozoh (Frontiers in Endocrinology, 2014)
Free fatty acids (FFAs) are essential nutrients and act as signaling molecules in various cellular processes via binding with FFA receptors. Of these receptors, GPR43 is activated by short chain fatty acids (SCFAs; e.g., acetate, propionate, and butyrate). During feeding, SCFAs are produced by microbial fermentation of dietary fiber in the gut, and these SCFAs become important energy sources for the host. The gut microbiota affects nutrient acquisition and energy regulation of the host and can influence the development of obesity, insulin resistance, and diabetes. Recently, GPR43 has been reported to regulate host energy homeostasis in the gastrointestinal tract and adipose tissues. Hence, GPR43 is also thought to be a potential drug target for metabolic disorders, such as obesity and diabetes. In this review, we summarize the identification, structure, and activities of GPR43, with a focus on host energy regulation, and present an essential overview of our current understanding of its physiological roles in host energy regulation that is mediated by gut microbiota. We also discuss the potential for GPR43 as a therapeutic target.